Pengembangan Modul Tata Rias Wajah pada Program Beauty Class Reporter Narasi TV - Alifia Sani Husen; Nurul Hidayah; Aniesa Puspa Arum (Journal on Education, 2025)
This research was developed through the lack of learning media used in the beauty class program specifically for reporters held on a television station, especially Narasi TV. This study aims to develop a make-up module in a beauty class aimed at TV station reporters. Television reporters need appropriate make-up skills to support a professional appearance through outdoor broadcasts and in the studio. This module is designed to meet these needs by providing systematic, easy-to-understand guidance that is in accordance with professional beauty standards. The research method used is Research and Development (R&D) with a 4D development model (define, design, develop, disseminate). The data collection technique uses a questionnaire distribution in the form of a questionnaire with qualitative and quantitative data analysis techniques. The results of the study showed that the feasibility value obtained by media experts was 100% and the results of the material expert validity test were carried out in 2 stages with a final value of 87%. Meanwhile, in the trial, students received a one-to-one assessment of 88.6% and in small groups of 88.4%. Based on the data obtained, it can be concluded that the Makeup module in the Narasi TV Beauty Class Reporter is said to be "very Appropriate" and "Very Practical" to be used as a guidebook for running a beauty class.